HUBUNGAN PERILAKU PENGGUNAAN MASKER DENGAN KEJADIAN MASK INDUCED ACNE PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2018 - ANGGRAINI BARUS; ARRIDHA UTAMI PUTRI (JURNAL ILMIAH SIMANTEK, 2022)
Coronavirus Disease 2019 (COVID-19) is a respiratory infection disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which was first discovered in Wuhan, China on December 31, 2019 and has spread throughout the world. Wearing a mask is the first step in preventing COVID-19. During a pandemic like this, people wear masks more often and for longer than before. It caused an incident of akne lokalisata in the area covered by the mask, which is popularly referred to as "mask induced acne". In addition to wearing masks for a long time, mask induced acne is also caused by poor mask wearing behavior. The purpose of this study was to determine the relationship between mask wearing behavior and the incidence of mask induced acne in students of the Faculty of Medicine, University of Muhammadiyah North Sumatra class of 2018. This study used an analytical description design with the Cross sectional method. The sample in this study was 57 people using a simple random sampling technique. Data collection was obtained from primary data by conducting anamnesis, physical examination and filling out questionnaires at students of the Faculty of Medicine, University of Muhammadiyah North Sumatra class of 2018. Furthermore, the data is analyzed using the Chi-square test. The results of the study were obtained from 26 respondents who behaved well, there were 11 respondents (42.35%) who suffered from mask induced acne and from 31 respondents who behaved adequately there were 25 respondents (80.6%) who suffered from mask induced acne. From the results of the Chi-square test, it was found that there was a significant relationship between mask wearing behavior and the incidence of mask induced acne (p = 0.003).